2022
DOI: 10.1002/admi.202101963
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Printing of Solution‐Processed 3D ZnO Nanostructures with Ultra‐High Yield for Flexible Metasurface Color Filter

Abstract: This work describes a facile thermal transfer printing process for solution‐processed high‐quality ZnO nanostructures. Nanostructures are synthesized through patterned solution growth and transfer‐printed onto a polymer substrate with an inverted configuration. Thus, the shape of the solution‐processed ZnO nanostructures can be regulated to have diversified forms, clearly defined edges, and improved surface profiles. To further demonstrate the scalability of such transfer printing process, a metasurface color … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
(47 reference statements)
0
5
1
Order By: Relevance
“…The optimized geometries exhibit a single sharp resonance response representing all the colors across the visible regime. To the best of our knowledge, our research outcomes exceed the previous findings documented in the literature, positioning our color filter as the foremost advancement in terms of vividness and overall performance 8 , 29 , 34 36 .…”
Section: Introductioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The optimized geometries exhibit a single sharp resonance response representing all the colors across the visible regime. To the best of our knowledge, our research outcomes exceed the previous findings documented in the literature, positioning our color filter as the foremost advancement in terms of vividness and overall performance 8 , 29 , 34 36 .…”
Section: Introductioncontrasting
confidence: 79%
“…Furthermore, we have conducted a full-wave simulation with finite structure to identify the number of required periods to retrive the results of a single unitcell simulation with periodic boundary conditions (for more details, the reader can refer to the supplementary information ). To the best of our knowledge, the optimized metasurface designs yield the most vivid color filter reported so far in the literature 8 , 29 , 34 36 . It is worth mentioning that the entire optimization process took 2 h, 37 min, and 45 s. Among this time, 1 h, 26 min, and 20 s were dedicated to simulations, 1 h, 2 min, and 6 s were allocated for back-propagation optimization, 8 min and 27 s were spent on predictions using both the surrogate model and the MVANN, and 250 ms were utilized for searching the best design within the dataset.…”
Section: Inverse Designmentioning
confidence: 93%
“…While Si has a high refractive index, its unavoidable absorption losses at short wavelengths result in low efficiency and reduced saturation due to the broadening of the bandwidth in visible range. To address the optical characteristics of the material itself, researchers have turned to dielectric materials with negligible losses in the visible light range, such as titanium dioxide (TiO2) [141143] , silicon nitride (Si3normalN4) [144146] , and so on [51,147,148] . Among these, TiO2, with its excellent optical properties and compatibility with CMOS processes, has found extensive use in the field of optics [149151] .…”
Section: Static Structural Colorsmentioning
confidence: 99%
“…Liu et al demonstrated the scalability of the transfer printing process through the fabrication of 300 μm×500 μm “windmill” ZnO patterns including more than 300,000 nanorod units on PC film [Fig. 5(b), i and iii] [109] . Further, to overcome the adhesion strength between the structures and target substrates, poly(methyl methacrylate) (PMMA) was chosen as the protection and transfer layer because of its high Young’s modulus (5 GPa) in the solidified PMMA polymer.…”
Section: Soft Lithographymentioning
confidence: 99%